An Analytical Review On Solar Water Heater - E.Srikanth Reddy, P.Vijay K. Raja Sekhar (International Journal of Scientific Research and Management (IJSRM), 2013)
Solar water heater has comprehensive variety of functions in homely as well as industrial category requirements of hot water. According to Renewable Energy Policy Network data (2011), more than 90 million people feel necessity for daily use of hot water. Solar water heater is not only eco-friendly but desires minor maintenance and operation cost compared with any other solar operating devices. It also consists of very low energy payback of 2 years to 3 years time. Generallysolar water heater is consists of two types so called active solar water heater and passive solar water heater. This review explains about researches conducted on solar water heater by various researchers of the world.